Analysis of Securitization In EU-Policy on the 2015-2018 Immigrant Crisis - Azachwa, Aurumma; Haqqi, Halifa; Wijayati, Hasna (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Europe experienced an immigrant crisis in 2015 which made the European Union to respond to the immigrant crisis. Thisresearch analyzes the policy of the European Union on the 2015-2018 immigrant crisis in the theory of securitization. Thepurpose of this research is to find out how the analysis of the theory of securitization in the European Union's policy towardsimmigrants in 2015. This research uses a qualitative research method with the collection of data used is the Library Researchmethod. This research uses the theory of securitization and regionalism which is used to explain the position of the EuropeanUnion as a supranational body that regulates or has responsibility for its member countries. The result of this research is thatin the process of securitization it is seen that there are some right-wing figures from the member states of the European Unionwho strongly oppose the entry of Immigrants into European territory. In addition, there is the role of the media and socialorganizations that are anti-immigrant and have influenced the European Union in taking policies to deal with the immigrantcrisis. This proves that securitization has a strong influence in changing the point of view of an event. So, securitization canalso be implemented not only for refugee problems but for other problems.Keywords: European Union, Immigrant Crisis, Regionalism, Securitization